Parental Separation and the Formation of Economic Preferences - Sarah C. Dahmann; Nathan Kettlewell; Jack Lam (Institute of Labor Economics (IZA), 2022)
We estimate the effect of parental separation on the risk and trust attitudes of German adolescents using a large household survey dataset, which allows us to match respondents to their siblings and parents. Our results indicate that adolescents from separated families are less trusting but have the same risk tolerance as adolescents from non-separated families, even after conditioning on the attitudes of parents and other controls. This trust deficit persists into early adulthood. Moreover, for both trust and risk, we find that separation attenuates the transmission of preferences from father to child. Additional analyses point to reduced parental involvement and greater family conflict as potential mechanisms.
Keywords: J12; J13; D91; D81; 330; family dissolution; divorce; preferences; risk; trust; intergenerational transmission